THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDES OF YOUTH WOMEN TO PREVENTION OF LEVIATION IN THE WORKING AREA OF SINDAR RAYA PUSKESMAS SIMALUNGUN DISTRICT - Beta Hanindiya; Arsiaty; Mustaruddin (Universitas Efarina, 2021)
Based on the findings of the researchers, there were 5 young women in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, experiencing vaginal discharge. This research was conducted to find out whether there is a relationship between the knowledge and attitudes of young women towards preventive measures for vaginal discharge in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, in 2017. This type of research is descriptive with the population in this study being all young women in the Working Area of ​​the Sindar Raya Health Center, Regency Simalungun in 2017, namely 108 people who were sampled as many as 85 people using the simple random sampling technique, which is a simple random sampling method. The results of this study showed that the majority had good knowledge, namely 42 people (49.4%), while the minority had less knowledge, namely 17 people (20%). The majority had an attitude of agreeing, namely 58 people (68.2%), while a minority had an attitude of disagreeing, namely 27 people (31.8%). The majority had good leucorrhoea prevention measures as many as 57 people (67.1%) while the minority had bad leucorrhoea prevention measures as many as 28 people (32.9%). From the results of the chisguare test it can be concluded that knowledge has a relationship with preventive measures for the occurrence of vaginal discharge in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency in 2017. From the results of the chisguare test cross-table attitudes with actions, a p value of 0.000 is obtained. Likewise, attitudes have a relationship with preventive measures for the occurrence of leucorrhoea in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, 2017. 2%) while the minority had a disapproving attitude, namely 27 people (31.8%). The majority had good leucorrhoea prevention measures as many as 57 people (67.1%) while the minority had bad leucorrhoea prevention measures as many as 28 people (32.9%). From the results of the chisguare test it can be concluded that knowledge has a relationship with preventive measures for the occurrence of vaginal discharge in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency in 2017. From the results of the chisguare test cross-table attitudes with actions, a p value of 0.000 is obtained. Likewise, attitudes have a relationship with preventive measures for the occurrence of leucorrhoea in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, 2017. 2%) while the minority had a disapproving attitude, namely 27 people (31.8%). The majority had good leucorrhoea prevention measures as many as 57 people (67.1%) while the minority had bad leucorrhoea prevention measures as many as 28 people (32.9%). From the results of the chisguare test it can be concluded that knowledge has a relationship with preventive measures for the occurrence of vaginal discharge in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency in 2017. From the results of the chisguare test cross-table attitudes with actions, a p value of 0.000 is obtained. Likewise, attitudes have a relationship with preventive measures for the occurrence of leucorrhoea in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, 2017. 1%) while the minority had bad leucorrhoea prevention measures as many as 28 people (32.9%). From the results of the chisguare test it can be concluded that knowledge has a relationship with preventive measures for the occurrence of vaginal discharge in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency in 2017. From the results of the chisguare test cross-table attitudes with actions, a p value of 0.000 is obtained. Likewise, attitudes have a relationship with preventive measures for the occurrence of leucorrhoea in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, 2017. 1%) while the minority had bad leucorrhoea prevention measures as many as 28 people (32.9%). From the results of the chisguare test it can be concluded that knowledge has a relationship with preventive measures for the occurrence of vaginal discharge in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency in 2017. From the results of the chisguare test cross-table attitudes with actions, a p value of 0.000 is obtained. Likewise, attitudes have a relationship with preventive measures for the occurrence of leucorrhoea in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, 2017. From the results of the chisguare test it can be concluded that knowledge has a relationship with preventive measures for the occurrence of vaginal discharge in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency in 2017. From the results of the chisguare test cross-table attitudes with actions, a p value of 0.000 is obtained. Likewise, attitudes have a relationship with preventive measures for the occurrence of leucorrhoea in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, 2017. From the results of the chisguare test it can be concluded that knowledge has a relationship with preventive measures for the occurrence of vaginal discharge in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency in 2017. From the results of the chisguare test cross-table attitudes with actions, a p value of 0.000 is obtained. Likewise, attitudes have a relationship with preventive measures for the occurrence of leucorrhoea in the Working Area of ​​the Sindar Raya Health Center, Simalungun Regency, 2017.